Organizational Commitment Based on Contribution from WFH, Organizational Culture, and Work Motivation at the Badan Keuangan and Aset Daerah Kota Kupang - Luis Marnisah; Rosina Ravenska Mbuik; Jefirstson Richset Riwukore (Mahesa Research Center, 2022)
The purpose of this study was to analyze and prove the effect of WFH, organizational culture and work motivation on employee organizational commitment. This research was carried out for 5 months (January-May 2022) at the Office of the Badan Keuangan and Aset Daerah Kota Kupang. This research is classified as a quantitative study using a confirmative verification (associative) survey method. The research population was 103 employees whose sample was determined based on the census technique (saturated sample) so the sample was 103 respondents. The type of research data consists of primary data and secondary data. Techniques to obtain data using questionnaires (Likert scale), interviews, and documentation. Data analysis used multiple linear regression analysis (partial test and simultaneous test). The results showed that the variables of WFH, organizational culture, and work motivation had a positive and significant effect on organizational commitment, either partially or simultaneously. This is because the entire t-count value obtained by each variable is greater than the t-table and also the F-count is greater than the F-table with a significance value less than 0.05. The results of this study also show the contribution of the WFH variable to an organizational commitment by 82.1%, organizational culture to an organizational commitment by 33.0%, and work motivation to an organizational commitment by 66.1%. Simultaneously, the contribution of WFH, organizational culture, and work motivation to organizational commitment is 83.3%.